Comprehensive analysis and validation of the prognostic value of glycosylation- and mitophagy-related genes for head and neck squamous cell carcinoma - Lu, Qiaoling; Ying, Li; Ling, Lang; Hui, Wu; Wang, Xinbin (Translational Cancer Research, 2026)
The treatment of head and neck squamous cell carcinoma (HNSCC) is particularly difficult because of its aggressive nature, complex anatomical location, and high recurrence and metastasis rates. This study investigated the relationship between glycosylation and mitophagy-related genes in HNSCC.